Effectiveness of Lesson Exemplars on the Work Performance of Teachers in Public Elementary Schools - Patinio, Casey Lyn (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effectiveness of lesson exemplars on the work performance of public elementary school teachers in the Jalajala District, Schools Division Office of Rizal during the School Year 2025–2026. Eight schools participated, with 141 teacher-respondents out of a total population of 154. Respondents were described by age, sex, civil status, educational attainment, position title, length of service, and in-service trainings.A descriptive survey research design and documentary analysis were employed. Data were gathered using a researcher-made questionnaire-checklist assessing perceived effectiveness of lesson exemplars in motivational, instructional, and evaluation skills. Teachers’ work performance was measured through their Individual Performance Commitment and Review (IPCR) results for 2024–2025.Findings revealed that lesson exemplars are highly effective in enhancing teachers’ motivational, instructional, and evaluation skills. Perceptions of effectiveness varied significantly by age, educational attainment, length of service, position title, and in-service trainings, but not by sex or civil status. Teachers’ work performance was very satisfactory, and a significant correlation was found between perceived effectiveness of lesson exemplars and work performance.The study concluded that professional characteristics influence perceived effectiveness of lesson exemplars, which is associated with improved teacher performance. It is recommended that administrators offer targeted professional development, encourage refinement and sharing of lesson exemplars, and integrate teacher feedback in exemplar design. Further studies considering additional variables are suggested
Keywords: Lesson exemplars, teacher performance, public elementary schools, motivational skills, instructional skills, evaluation skills